Ulinastatin Suppresses Burn-Induced Lipid Peroxidation and Reduces Fluid Requirements in a Swine Model. (24th April 2013) - Luo, Hong-Min; Du, Ming-Hua; Lin, Zhi-Long; Hu, Quan; Zhang, Lin; Ma, Li; Wang, Huan; Wen, Yu; Lv, Yi; Lin, Hong-Yuan; Pi, Yu-Li; Hu, Sen; et al.
Abstract : Objective . Lipid peroxidation plays a critical role in burn-induced plasma leakage, and ulinastatin has been reported to reduce lipid peroxidation in various models. This study aims to examine whether ulinastatin reduces fluid requirements through inhibition of lipid peroxidation in a swine burn model. Methods . Forty miniature swine were subjected to 40% TBSA burns and were randomly allocated to the following four groups: immediate lactated Ringer's resuscitation (ILR), immediate LR containing ulinastatin (ILR/ULI), delayed LR resuscitation (DLR), and delayed LR containing ulinastatin (DLR/ULI). Hemodynamic variables, net fluid accumulation, and plasma thiobarbituric acid reactive substances (TBARS) concentrations were measured. Heart, liver, lung, skeletal muscle, and ileum were harvested at 48 hours after burn for evaluation of TBARS concentrations, activities of antioxidant enzymes, and tissue water content. Results . Ulinastatin significantly reduced pulmonary vascular permeability index (PVPI) and extravascular lung water index (ELWI), net fluid accumulation, and water content of heart, lung, and ileum in both immediate or delayed resuscitation groups. Furthermore, ulinastatin infusion significantly reduced plasma and tissue concentrations of TBARS in both immediate or delayed resuscitation groups. Conclusions . These results indicate that ulinastatin can reduce fluid requirements through inhibition of lipid peroxidation.